2014
DOI: 10.1093/toxsci/kfu092
|View full text |Cite
|
Sign up to set email alerts
|

Toxicogenomics in the 3T3-L1 Cell Line, a New Approach for Screening of Obesogenic Compounds

Abstract: The obesogen hypothesis states that together with an energy imbalance between calories consumed and calories expended, exposure to environmental compounds early in life or throughout lifetime might have an influence on obesity development. In this work, we propose a new approach for obesogen screening, i.e., the use of transcriptomics in the 3T3-L1 pre-adipocyte cell line. Based on the data from a previous study of our group using a lipid accumulation based adipocyte differentiation assay, several human-releva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 31 publications
4
31
0
Order By: Relevance
“…Under the present investigation, we observed that gene expression changes resulting from the exposure may indeed reflect an investigational approach that highlights biomarkers of specific diseases and disorders, e.g. metabolic disorders (including obesity and diabetes) cardiovascular, endocrine disruption, and cancers, in accord with results observed in epidemiological settings (Langer et al, 2014; Arrebola et al, 2014; Recio-Vega et al, 2013; Lee et al, 2014; Wadzinski et al, 2014; Pereira-Fernandes et al, 2014; Sexton et al, 2013, Casas et al, 2014). Research utilizing PBMC cells in human are now being widely used to test for the efficacy of new drugs and treatments, to divulge the differential gene expression patterns induced by toxicity, and to study downstream effectors, all of which can be used as a potential source for developing disease-specific biomarkers (Reynes et al, 2014; Saidijam et al, 2014; Roccaet et al, 2014; Kong 2014).…”
Section: Discussionsupporting
confidence: 80%
“…Under the present investigation, we observed that gene expression changes resulting from the exposure may indeed reflect an investigational approach that highlights biomarkers of specific diseases and disorders, e.g. metabolic disorders (including obesity and diabetes) cardiovascular, endocrine disruption, and cancers, in accord with results observed in epidemiological settings (Langer et al, 2014; Arrebola et al, 2014; Recio-Vega et al, 2013; Lee et al, 2014; Wadzinski et al, 2014; Pereira-Fernandes et al, 2014; Sexton et al, 2013, Casas et al, 2014). Research utilizing PBMC cells in human are now being widely used to test for the efficacy of new drugs and treatments, to divulge the differential gene expression patterns induced by toxicity, and to study downstream effectors, all of which can be used as a potential source for developing disease-specific biomarkers (Reynes et al, 2014; Saidijam et al, 2014; Roccaet et al, 2014; Kong 2014).…”
Section: Discussionsupporting
confidence: 80%
“…Several laboratories have shown that TBT stimulates adipogenesis in preadipoctyes in vitro [369-371] [372]. Prenatal exposure to TBT results in increased lipid accumulation, increased adipose tissue mass (due to both adipocyte hyperplasia and hypertrophy), and reduced muscle mass that persists into adulthood and across generations in mouse models [309, 367] and increased adiposity in zebrafish [373].…”
Section: Mdcs and Metabolism-relevant Diseasesmentioning
confidence: 99%
“…In studies involving induction of differentiation events from embryos or stem cells, prolonged treatment of up to two weeks in vitro revealed similar small numbers of genes induced or repressed by EDCs [71]. The numbers of affected genes can be much higher for specialized somatic cell lines [72]. In studies of ES or pluripotent cell exposures to higher EDC doses for short periods of 72 h or less, larger numbers of affected genes are seen for some EDCs [7375], but small numbers for others [75].…”
Section: Discussionmentioning
confidence: 99%